Generative Repair and Graceful Decay: Interview with Caitlin DeSilvey - Caitlin DeSilvey; Blanca Callén; Melisa Duque (Diseña, 2023)
Professor Caitlin DeSilvey works as a cultural geographer and lecturer at the University of Exeter. Her work explores the ways in which built environments change through aging, including processes of repair, decay, and wasting. She collaborates with photographers, architects, designers, repairers, heritage practitioners, and with students in her teaching. DeSilvey fosters sensibilities of how to collaborate with the buildings and structures that ‘tell us what they need’, and with the living ecologies that contribute to the transformation of these decaying matters, ‘to allow them space in the future’ of these environments.